The Effects of Augmented Reality Visual Cues on Turning in Place in Parkinson's Disease Patients With Freezing of Gait - Janssen, Sabine; de Ruyter van Steveninck, Jaap; Salim, Hizirwan S.; Cockx, Helena M.; Bloem, Bastiaan R.; Heida, Tjitske; van Wezel, Richard J. A. (Frontiers in Neurology, 2020)
Background: Turning in place is particularly bothersome for patients with Parkinson’s disease (PD) experiencing freezing of gait (FOG). Cues designed to enforce goal-directed turning are not yet available. Objectives: Assess whether augmented reality (AR) visual cues improve FOG and turning in place in PD patients with FOG. Methods: Sixteen PD patients with FOG performed a series of 180 degree turns under an experimental condition with AR visual cues displayed through a HoloLens, and two control conditions (one consisting of auditory cues; and one without any cues). FOG episodes were annotated by two independent raters from video recordings. Motion data were measured with 17 inertial measurement units for calculating axial kinematics, scaling and timing of turning. Results: AR visual cues did not reduce the percent time frozen (p 0.73), nor the number (p 0.73) and duration (p 0.78) of FOG episodes compared to the control condition without cues. All FOG parameters were higher with AR visual cues than with auditory cues (percent time frozen (p 0.01), number (p 0.02) and duration (p 0.007) of FOG episodes). The AR visual cues did reduce the peak angular velocity (visual vs. uncued p 0.03; visual vs. auditory p 0.02) and step height (visual vs. uncued p 0.02; visual vs. auditory p 0.007), and increased the step height coefficient of variation (visual vs. uncued p 0.04; visual vs. auditory p 0.01) and time to maximum head-pelvis separation (visual vs. uncued p 0.02; visual vs. auditory p 0.005), compared to both control conditions. Conclusions: The AR visual cues in this study did not reduce FOG, and worsened some measures of axial kinematics, and turn scaling and timing. Stimulating goal-directed turning might, by itself, be insufficient to reduce FOG and improve turning performance.